2016
DOI: 10.1038/tp.2016.188
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex-specific urinary biomarkers for major depressive disorder by combined application of NMR- and GC–MS-based metabonomics

Abstract: Women are more vulnerable to major depressive disorder (MDD) than men. However, molecular biomarkers of sex differences are limited. Here we combined gas chromatography–mass spectrometry (GC–MS)- and nuclear magnetic resonance (NMR)-based metabonomics to investigate sex differences of urinary metabolite markers in MDD, and further explore their potential of diagnosing MDD. Consequently, the metabolite signatures of women and men MDD subjects were significantly different from of that in their respective healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 31 publications
(36 reference statements)
2
36
0
Order By: Relevance
“…Even under the assumption of well consistency in patients’ fundamental conditions, there performs still huge individual variations among each patient. [ 19 , 20 ] These differences may result from diverse eating habits, educational background, living environment, etc, which may demonstrate why different studies utilizing metabolomics for the same disease tend to reach various outcomes. Considering that the metabolome is sensitive to external factors, especially diet and sleeping schedules, we adopted the design of the patient before and after a control experiment to manage this uncontrollable factor.…”
Section: Discussionmentioning
confidence: 99%
“…Even under the assumption of well consistency in patients’ fundamental conditions, there performs still huge individual variations among each patient. [ 19 , 20 ] These differences may result from diverse eating habits, educational background, living environment, etc, which may demonstrate why different studies utilizing metabolomics for the same disease tend to reach various outcomes. Considering that the metabolome is sensitive to external factors, especially diet and sleeping schedules, we adopted the design of the patient before and after a control experiment to manage this uncontrollable factor.…”
Section: Discussionmentioning
confidence: 99%
“…But this panel could only accurately predict 41.1% PPD subjects, which was significantly lower than the prediction accuracy of our panel identified in this study. Two reasons might cause this difference: 1) the panel identified by Zheng et al18 was used to diagnose depression and 2) all included subjects here were women, but the panel identified by Zheng et al18 did not take sex-based differences into consideration, since many studies reported that there were sex differences in depression 3032…”
Section: Discussionmentioning
confidence: 99%
“…This relationship was more pronounced in men than in women, with correlations of white blood cell deviations to Montgomery-Asberg depression rating scale (MADRS) score only reaching significance in the male subjects. Urinalysis studies using multiple methods have revealed sex-specific metabolite biomarkers for MDD, with higher diagnostic accuracy than non-sex-specific screens [232]. Together these studies highlight the need for sex-specific research in developing diagnostic biomarkers for depression.…”
Section: Biomarkersmentioning
confidence: 96%